Wholesale Distribution of Breakfast Cereals in Southern Michigan (Book). - Fellows, D. R. (The Accounting Review, 1934)
Reviews the book "Wholesale Distribution of Breakfast Cereals in Southern Michigan," by Edgar H. Gault and Raymond F. Smith.